Multicenter phase II study of abemaciclib and ramucirumab in metastatic esophageal/gastroesophageal junction carcinoma - Kelly, Ronan Joseph; Lam, Vincent K.; Paulson, Scott; Settele, Natalie; Sido, Oghenevovwero; Anagnostou, Valsamo; Raj, Moses S.; Zaidi, Ali Hussainy (Journal of clinical oncology, 2022)
TPS4169Background: Cyclin dependent kinases (CDKs) are serine/threonine kinases that are responsible for phosphorylating the intracellular proteins that coordinate cell-cycle progression. The Cancer Genome Atlas (TCGA) molecular analysis of esophageal/gastroesophageal junction (E/GEJ) carcinomas has highlighted significant dysregulation of CDKN2A, the gene coding for the tumor suppressor p16, through deletion, mutation or epigenetic silencing in up to 76% of cases and the associated significant upregulation of the CDK4/6-Cyclin D-axis (The Cancer Genome Atlas Research Network. Integrated genomic characterization of oesophageal carcinoma. Nature 2017). Preclinical experiments demonstrated that single agent abemaciclib has potent antitumor efficacy both in vitro and in vivo in esophageal adenocarcinoma with direct pathway inhibition (Kosovec J et al. CDK4/6 dual inhibitor abemaciclib demonstrates compelling preclinical activity against esophageal adenocarcinoma: a novel therapeutic options for a deadly disease. Oncotarget 2017 Nov 1;8[59]). Significant activity was seen in the OE33 (p=0.048) and FLO1 (p=0.043) esophageal cancer cell lines while western blot revealed downregulation of Cyclin D, phospho-pRb, E2F1, and Cyclin A2 (Kosovec J et al, 2017). In vivo experiments, utilizing the Levrat model of end-to-side esophagojejunostomy performed on Sprague-Dawley rats demonstrated that 78.9% of animals given abemaciclib demonstrated >20% tumor volume decrease (placebo 0%). Post treatment comparison between placebo and abemaciclib of qRT-PCR gene expression demonstrated downregulation of pathway correlates, including CDK4 (p=0.023), CDK6 (p=0.068), E2F1 (p=0.005), Rb1 (p=0.067), Cyclin D (p=0.031), and Cyclin A (p=0.039) (Kosovec J et al, 2017). The JPBJ phase 1b study has previously demonstrated the safety of combining abemaciclib with ramucirumab in NSCLC. Methods: Subjects with previously treated metastatic esophageal or gastroesophageal junction adenocarcinomas are eligible for this study which is currently open and enrolling patients. Squamous cell and mixed histology with neuroendocrine features are excluded. A total of 30 patients will be enrolled across 3 sites at Baylor University Medical Center in Dallas, The Allegheny Health Network in Pittsburgh and at Johns Hopkins Hospital in Baltimore. The primary objective is to describe the safety profile of abemaciclib (150mg po bid) and ramucirumab (8mg/kg iv every 2 weeks) in this patient population as assessed according to Common Terminology Criteria for Adverse Events version 4.0. Secondary objectives are to assess response rate, progression free and overall survival. In addition, we will determine the rate of stable disease at 3 months post targeted therapy. Correlative studies investigating changes in the expression of selected serum/tissue genomic markers of interest will be performed. Clinical trial information: NCT04921904.